2015
DOI: 10.4103/1119-3077.154218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-level laser therapy on osteoblastic bone formation and relapse in an experimental rapid maxillary expansion model

Abstract: Histologically, LLLT stimulated bone formation, as revealed by analysis after the retention period. LLLT during expansion may accelerate bone healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Although the biological mechanisms of low-level laser irradiation or low-level laser therapy/treatment (LLLT) have not been fully revealed, LLLT is a successfully and widely used non-pharmacological method for bone regeneration in experimental in vivo and in vitro models [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Current research suggests that LLLT stimulates the proliferation and differentiation of various cell types and promotes the repair process in vivo and in vitro : a wavelength of 600–904 nm and an output power of 1–500 mW; activation of ERK1/ERK2 and a phosphatidylinositol 3-kinase (PI3K) pathway; the increase of reactive oxygen species (ROS) and ATP/cyclic AMP; the absorption of light by a photoreceptor and the photoactivation of enzymes in the mitochondria; etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the biological mechanisms of low-level laser irradiation or low-level laser therapy/treatment (LLLT) have not been fully revealed, LLLT is a successfully and widely used non-pharmacological method for bone regeneration in experimental in vivo and in vitro models [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Current research suggests that LLLT stimulates the proliferation and differentiation of various cell types and promotes the repair process in vivo and in vitro : a wavelength of 600–904 nm and an output power of 1–500 mW; activation of ERK1/ERK2 and a phosphatidylinositol 3-kinase (PI3K) pathway; the increase of reactive oxygen species (ROS) and ATP/cyclic AMP; the absorption of light by a photoreceptor and the photoactivation of enzymes in the mitochondria; etc.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 ]. With respect to bone, LLLT has been shown to modulate inflammatory processes and bone repair [ 3 , 4 , 5 ], accelerate osteoblast proliferation and bone formation [ 6 , 7 , 8 , 9 , 10 ], and enhance bone healing [ 1 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that histologically, LLLT stimulated bone formation. 19 The effects of LLLT can also be seen on human cells, Khadra et al 2005 studied the effects of LLLT on attachment, proliferation and differentiation of human osteoblast-like cells cultured on titanium implant material using an 830nm Ga-Al-As diode laser. (Rønvig Dental AS, Denmark) Each culture dish was irradiated with 84mW at a dosage of 1.5 or 3J/cm 2 .…”
mentioning
confidence: 99%